If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1 = 97 + -5x Reorder the terms: -1 + 9x = 97 + -5x Solving -1 + 9x = 97 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -1 + 9x + 5x = 97 + -5x + 5x Combine like terms: 9x + 5x = 14x -1 + 14x = 97 + -5x + 5x Combine like terms: -5x + 5x = 0 -1 + 14x = 97 + 0 -1 + 14x = 97 Add '1' to each side of the equation. -1 + 1 + 14x = 97 + 1 Combine like terms: -1 + 1 = 0 0 + 14x = 97 + 1 14x = 97 + 1 Combine like terms: 97 + 1 = 98 14x = 98 Divide each side by '14'. x = 7 Simplifying x = 7
| (3x+4)=16 | | (3x^2+4)=16 | | 17n^2-10n-12=3n^2-8 | | H=(3a-20a)(2a+10) | | x/2+3x=180 | | 7-8p=9 | | 4+-2(2x+-7)=-6 | | 4-2(2x-7)=-5 | | 18p^2-55=30p-7 | | 8+2x=x+3 | | 8-2x=x+3 | | x-3+x=121 | | v^2+1=v | | 17+3x=(5-x) | | 4k^2+60k+216=0 | | 4n^2+16=-20n | | q=-7x^2+6x+4 | | (n-4)(n-5)=0 | | 10d-22+6y=12d+10 | | mn-x=m | | 0=4x^2-5x-5 | | 0=4x^2+5x-5 | | p=-5x^2+6x+6 | | x+36=x*4 | | 8x+2y+26=10 | | 13x^2+8x-22=0 | | 6+25x=20x+10 | | 5x+2(x+5)=52 | | f(x)=0.7 | | 4+7x=16+x | | (5x)(6y)= | | 6x-3=16x-38 |